Translation and psychometric properties of the German version of the University of the West of England Interprofessional Questionnaire (UWE-IP) - Mahler, Cornelia; Berger, Sarah; Krisam, Johannes; Szecsenyi, Joachim; Krug, Katja (Journal of interprofessional care, 2017)
The implementation of a bachelor degree in Interprofessional Health Care at the University of Heidelberg, Germany, has fostered the need to evaluate the impact of this innovative programme. The University of the West of England Interprofessional Questionnaire (UWE-IP) was developed for longitudinal evaluation of an interprofessional curriculum. The UWE-IP consists of 35 items in four scales: “Communication and Teamwork Scale,” “Interprofessional Learning Scale,” “Interprofessional Interaction Scale,” and “Interprofessional Relationships Scale.” The UWE-IP was translated to German according to international guidelines. Psychometrics were assessed: reliability of the four scales was tested with Cronbach‘s alpha and confirmatory factor analysis was performed to examine the underlying factor structure. The sample consisted of 326 datasets. Reliability for the scales was between 0.75 and 0.90. The underlying factor structure showed a good fit. We conclude that the German UWE-IP shows good psychometrics and recommend its use for evaluation of interprofessional learning activities. These results add to the body of knowledge on evaluation instruments in interprofessional education.
Published online 21 Oct 2016
Gesehen am 07.08.2018